microRNA-122 regulates hypoxia-inducible factor-1 and vimentin in hepatocytes and correlates with fibrosis in diet-induced steatohepatitis - Csak, Timea (Liver Int, 2014)
BACKGROUND & AIMS: miR-122 is the most abundant miRNA in the liver particularly in hepatocytes where it targets cholesterol metabolism. Steatosis, a key component of non-alcoholic fatty liver disease , is regulated by hypoxia-inducible factor-1α (HIF-1α). Here, we hypothesized that reduced miR-122 has a pathogenic role in steatohepatitis. METHODS: miR-122 and its target genes were evaluated in mouse livers and/or isolated hepatocytes after methionine-choline-deficient (MCD) or methionine-choline-supplemented (MCS) diet. RESULTS: Liver and hepatocyte miR-122 expression was significantly decreased in steatohepatitis. A maximum reduction in miR-122 occurred at the fibrosis stage (8 weeks of MCD diet). MAP3K3, a miR-122 target gene, was induced at all stages of NASH (3–8 weeks) only at the mRNA level. Increased NFκB activation was found in MCD diet-fed mice and MAP3K3 regulated the NFκB DNA binding in naive hepatocytes. . HIF-1α mRNA and DNA binding and expression of the HIF-1α target gene, pro-fibrotic lysil oxidase , was increased in advanced steatohepatitis (8 weeks). In addition, increase in vimentin and Sirius red staining (liver fibrosis) was found at 8 weeks of MCD diet. Using miR-122 over-expression and inhibition approaches we confirmed that HIF-1α, vimentin and MAP3K3 are novel miR-122 targets in hepatocytes. We report transcriptional repression of miR-122 in NASH. Decreased liver miR-122 was associated with elevated circulating miR-122 in both exosome-rich and protein-rich serum fractions. CONCLUSIONS: Our novel data suggest that decreased liver miR-122 contributes to upregulation of modulators of tissue remodeling (HIF-1α, vimentin and MAP3K3) and might play a role in NASH induced liver fibrosis.